Investigating the cost-effectiveness of antiplatelet medications in patients with type 2 diabetes for the secondary prevention of acute coronary syndromes - Gkountouras, Georgios (2020)
Acute Coronary Syndrome (ACS) is a condition with very high clinical burden and financial burden worldwide and in the UK. ACS is more common in populations with Type 2 Diabetes Mellitus(T2DM), due to the vascular complications that people with T2DM face. This fact results in increased occurrence of ACS compared to the general population. ACS management is complex in T2DM populations because of the additional need for glycaemic control. Oral antiplatelet medication (clopidogrel, aspirin) is among the most important treatments for the secondary prevention of ACS.